Neoadjuvant Biologic Therapy in the Surgical Management of Patients with Hidradenitis Suppurativa: A Cohort Study - Luis Salvador-Rodriguez; Carlos Cuenca-Barrales; Salvador Arias-Santiago; Alejandro Molina-Leyva (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)